Performance of Soft Soil Improved Prefabricated Vertical Drain (PVD) for Road Construction in Pontian, Johor - IBRAHIM, MUHAMAD IZZAIRIN AZIM; YUSOF, MOHD FAIRUS (Recent Trends in Civil Engineering and Built Environment, 2023)
Construction on soft soil deposit is a major challenge in the field of geotechnical engineering as many engineering problems in the form of slope instability, lack of capacity or excessive settlement may arise either during or after the construction process due to the low shear strength and high compressibility of this soil. Hence, this study focusing on the performance of soft soil improved PVD for road construction in Pontian, Johor as a method of soil improvement. The objective of this study is to model the road improved by PVD using PLAXIS 2D software, thus the determination of the settlement behavior of the proposed model using varies penetration length (100%, 75% and 50%) and spacing (1 m, 1.5 m and 2 m) of PVD can be made. The soft soil layer was model using Soft Soil model and Mohr-Coulomb model. The result proved that the rate of settlement (d100) is faster at PVD with spacing 1 m, and using spacing 1m also decrease the time taken to reach minimum excess pore pressure. Models with varies length, however do not have significant differences in term of rate of settlement and time taken to reach minimum excess pore pressure. So, the most suitable design recommended to be applied for the road construction in Pontian Johor is using alternating PVD length with 50% penetration length and with 1 m spacing.